Policy-making and institutional crisis: Formalizing artisanal gold mining in Zimbabwe from 2005 to 2017 - Mukonoweshuro, Tonderai Fadzai (Policy-making and institutional crisis: Formalizing artisanal gold mining in Zimbabwe from 2005 to 2017, 2024)
Artisanal gold mining is a crucial economic activity in Zimbabwe that gained prominence in the post-2000 period when there was a defined shifting interest from agricultural activity by many people to artisanal gold mining, with over a million people engaged in the sector. Artisanal gold mining became a part of a large and complex informal economy, with the potential to address some of the economic challenges by providing the much-needed foreign currency for the ailing economy. However, like most countries, Zimbabwe struggled to regulate the sector to make it more efficient, economical, safe and environmentally friendly. Much existing research seems to suggest that policy on artisanal mining, while being a function of the state, is an instrument or arena of contestation among powerful groups within the state and society. Thus, the study answers the question, “In what ways did politics, power and institutional dynamics influence policy trajectories on artisanal gold mining in Zimbabwe between 2005 and 2017?” It further investigated the complex reality of politics and policymaking for informal (artisanal) gold mining in Zimbabwe, seeking to dissect underlying politics, power and institutional dynamics and how these influenced policy trajectories in this growing informal gold mining sector between 2005 and 2017. Through a case study approach, I collected qualitative data through in-depth individual interviews with key informants both nationally and at two mining sites in the District of Chegutu, in Mashonaland, Zimbabwe. By situating the study's findings within theories of informal economies, institutionalism, street-level bureaucracy and human securities, this thesis contributes to the consequences of informality as they relate to production and the miners 6 wellbeing and policy development for ASM. The other is the complex and non-linear reality of politics and policy-making concerning ASM and law enforcement agencies. The local case study demonstrates the struggles between networked actors in amplifying how informal gold mining policy has evolved and the particular effects on policy outcomes for informal gold mining in Zimbabwe. The study concluded that although politics had a bearing on the continued informalisation of ASM during the crisis period, the state actors occupying critical positions in shadow networks drove policy to maximize self-interest. At a local level, policy implementation met the agency of transitional actors, including small-scale artisanal miners, gold dealers, and traders. These networked actors also operated within their own unwritten rules and shaped their policies as they extracted or traded the gold. Therefore, a policy framework for formalizing ASM must be based on enforceable legal systems that provide accountability, transparency, and human rights.
A research report submitted in partial fulfillment of the requirements for the degree of Doctor of Philosophy to the Faculty of Commerce, Law, and Management, Wits School of Governance, University of the Witwatersrand, Johannesburg, 2024
Keywords: Institutions; Informal economies street-level bureaucracies and human security; SDG-7: Affordable and clean energy